Double Burden Laki-Laki Terhadap Anak Dalam Novel 'Aysel' Karya Imre Mehmet - Ilyas, Muhammad Azizzullah; Yazid, Muhammad Abduh (Kitabina: Jurnal Bahasa dan Sastra Arab, 2021)
Men taking care of children are at taboo according to some societies, especially for bachelors. In fact, in some cultures, bachelors who care for children seem lowly and not authoritative considering the position of the man as the head of the family. This study seeks to explore the concept of the male double burden in the household in the novel Aysel by Imre Mehmet. In addition, this novel also examines how communication is built by a man in caring for and children, build emotional and spiritual values. This study uses a qualitative approach with a receptive analysis of literature. This study found that Aysel's novel contains a cultural message of Turkish society, the double burden experienced by Iskender is unique, where a bachelor becomes a single parent even though it is only temporary, and in Turkey this phenomenon is something unusual. In addition, religious and moral messages are embedded in Aysel and Iskender's dialogue, making this novel more alive and real.